The effect of stored barley cultivars, temperature and humidity on population increase of Acarus siro, Lepidoglyphus destructor and Tyrophagus putrescentiae - Hubert, Jan; Pekár, Stano; Aulický, Radek; Nesvorná, Marta; Stejskal, Václav (Experimental & applied acarology, 2013)
The rate of population increase of three mite species, Acarus siro (L.), Lepidoglyphus destructor (Schrank) and Tyrophagus putrescentiae (Schrank), was studied on various types of barley and at various combinations of temperature and humidity. The mites were added into the chambers and incubated for 21 days on seven different kinds of barley coming from four sites, including six cultivars and a mixture. The population increase of all species was higher on the mixture than on any other cultivar, except for Sebastian and Calgary. The increase of mites was studied at constant temperatures ranging from 5 to 35 °C and relative humidity (RH) ranging from 50 to 90 %. Positive rate of increase was found above 70 % RH for all species. The optimal humidity was at 85 % RH for A. siro and L. destructor and at 90 % RH for T. putrescentiae. As concerns the temperature, positive rate of increase was found at temperatures higher than 10, 15 and 20 °C for A. siro, L. destructor and T. putrescentiae, respectively. The temperature optima were at 23, 25, and 30 °C for A. siro, L. destructor and T. putrescentiae, respectively. Model estimated on laboratory data was then fitted to temperature and humidity records from August to November in the Czech grain store. Estimated population rate of increase was rarely positive: for A. siro it was for 24 %, for L. destructor for only 1 % and for T. putrescentiae for only 7 % days of the study period. It is concluded that in the climatic conditions of the Czech Republic the population increase of three mite pests is negligible during autumn and winter.
Keywords: Hordeum; Acari; Temperature; Population Dynamics; Humidity; teplota; Animals; ječmen (rod); populační dynamika; zvířata; vlhkost